2001
DOI: 10.1207/s15327957pspr0503_3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Parental Caregiving

Abstract: Evolution, of course, occurs through genes. The metaphor of competing genes is illuminating but, as far as we know, genes do not take an active part in their survival, notwithstanding the anthropomorphic survival "strategies" and teleological "designs" described by some authors (Axelrod, 1984;Clutton-Brock, 1991;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 58 publications
0
55
0
Order By: Relevance
“…First, previous studies showed that women are more empathetic than men (Rueckert and Naybar 2008), which may allow them to be more responsive and sensitive to their child's needs. Second, mothers are biologically and evolutionarily better prepared than men to assume the caregiving role (Bell 2001). For instance, the increase in the production of several hormones, such as oxytocin, during the pregnancy and lactation periods facilitates caregiving, making mothers more sensitive to their child's needs (Dozier 2000).…”
Section: Discussionmentioning
confidence: 99%
“…First, previous studies showed that women are more empathetic than men (Rueckert and Naybar 2008), which may allow them to be more responsive and sensitive to their child's needs. Second, mothers are biologically and evolutionarily better prepared than men to assume the caregiving role (Bell 2001). For instance, the increase in the production of several hormones, such as oxytocin, during the pregnancy and lactation periods facilitates caregiving, making mothers more sensitive to their child's needs (Dozier 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is now generally agreed that one of the key evolutionary changes that emerged with the mammals was attachment and care provision for infants (Bell, 2001;Bowlby, 1969;Mikulincer & Shaver, 2004). In fact, many mammals (and especially humans) need, and are responsive to, signals of care and affection and have evolved attachment mechanisms that are sensitive and responsive to such signals (although some theorists distinguish warmth/affection from attachment/security/protection (MacDonald, 1992)).…”
Section: The Human Warmth Systemmentioning
confidence: 99%
“…Persons who are infected by HIV infection have a need to be, and are said to be, aware of the ethical ramifications of exposing their sex partners and to assume responsibility to protect their partners (Marks et al, 1999). The motivation to meet another's needs has been shown to have a neurobiological basis as a support for partner protection in close relationships (Bell, 2001;Kunce & Shaver, 1994;Panksepp, 1998). According to partner protection theory, having a HIV positive partner will predict lower sex risks in a relationship because the HIV positive person will want to protect the partner.…”
Section: Partner Protectionmentioning
confidence: 99%